David Huron, Voice Leading: The Science Behind a Musical Art (Cambridge, MIT Press, 2016) - Bernardes, Gilberto (Revista Portuguesa de Musicologia, 2017)
Recensão: David Huron, Voice Leading: The Science Behind a Musical Art (Cambridge, MIT Press, 2016) viii + 263 pp. ISBN: 9780262034852